Effect of moisture content of recycled aggregates on workability, compressive strength and durability of concrete-A review - Lu, Jun; Bao, Deming; Jin, Mingyang; Li, Ran; Gao, Yueqing; Hou, Shaodan; Liang, Chaofeng (Journal of Asian Concrete Federation, 2023)
It is necessary to clarify the influence of different moisture contents of recycled aggregates (RA), including oven dry (OD), saturated surface dry (SSD), air dry (AD), etc., on the performance of recycled aggregate concrete (RAC) considering the time-dependent water absorption characteristic of RAs. By analyzing the previous literature, the effects of different moisture contents of RAs on the workability, compressive strength, and durability of RAC were discussed in detail. In addition, the microscopic mechanism was revealed based on the microstructure analysis. A lot of studies have shown that RAC prepared with RA in OD state had the largest fluidity when the same additional water was used. The slump loss of RAC decreases with the increase of water content of RAs, and when the moisture content of RA is higher than 50% of the water absorption of SSD, the slump loss is related to the additional method. The compressive strength and durability of RAC prepared with RAs in AD state were better than that prepared with RA in OD or SSD state. The shrinkage of RAC prepared with RA in OD state was greater than that prepared with RA in the SSD or AD state.